2021
DOI: 10.1021/acsami.1c13701
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Plasmonic/Photonic Nanoscale Strategy for Multilevel Anticounterfeit Labels

Abstract: Innovative goods authentication strategies are of fundamental importance considering the increasing counterfeiting levels. Such a task has been effectively addressed with the so-called physical unclonable functions (PUFs), being physical properties of a system that characterize it univocally. PUFs are commonly implemented by exploiting naturally occurring nonidealities in clean-room fabrication processes. The broad availability of classic paradigm PUFs, however, makes them vulnerable. Here, we propose a hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 69 publications
0
46
0
Order By: Relevance
“…The design and development of novel encoded surfaces are of great research interest in today's world for use in anti-counterfeiting and authentication applications. Although the majority of encoded surface applications relate to the prevention of light, [20,21] carbon nanotubes, [22] spherical [23,24] and rod shaped [25] plasmonic nanoparticles, silver nanoislands, [26] core-shell nanoparticles, [27] polymeric particles, [28] diamonds, [29] and fluorescent compounds. [30] For the development of PUFs, fluorescent compounds are particularly interesting because they allow for rapid and simple authentication with multiple and interactive challenge-response pairs using facile and well-developed spectroscopic/microscopic techniques and portable tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and development of novel encoded surfaces are of great research interest in today's world for use in anti-counterfeiting and authentication applications. Although the majority of encoded surface applications relate to the prevention of light, [20,21] carbon nanotubes, [22] spherical [23,24] and rod shaped [25] plasmonic nanoparticles, silver nanoislands, [26] core-shell nanoparticles, [27] polymeric particles, [28] diamonds, [29] and fluorescent compounds. [30] For the development of PUFs, fluorescent compounds are particularly interesting because they allow for rapid and simple authentication with multiple and interactive challenge-response pairs using facile and well-developed spectroscopic/microscopic techniques and portable tools.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Starting from the seminal work by Pappu et al., [ 6 ] optical PUF systems have been an active research area. [ 10–17 ] In the past decade, a range of material types and manufacturing routes have been studied to demonstrate PUFs using silica microparticles, [ 6 ] inherent randomness of surfaces, [ 18,19 ] randomly positioned scatterers challenged by quantum states of light, [ 20,21 ] carbon nanotubes, [ 22 ] spherical [ 23,24 ] and rod shaped [ 25 ] plasmonic nanoparticles, silver nanoislands, [ 26 ] core‐shell nanoparticles, [ 27 ] polymeric particles, [ 28 ] diamonds, [ 29 ] and fluorescent compounds. [ 30 ]…”
Section: Introductionmentioning
confidence: 99%
“…As a result, advanced luminescent materials with unconventional excitation and emission modes including long-afterglow, 15 photon upconversion, 16,17 stimuli-responsive luminescence, 18 etc. 19,20 have been required for multidimensional anti-counterfeiting with high security levels. [21][22][23] Besides anti-counterfeiting, long-afterglow (also called longpersistent) luminescence has also been applied in bioimaging, sensing, emergency lighting and information storage 24,25 due to the self-sustain luminescence feature.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, advanced luminescent materials with unconventional excitation and emission modes including long-afterglow, 15 photon upconversion, 16,17 stimuli-responsive luminescence, 18 etc. 19,20 have been required for multi-dimensional anti-counterfeiting with high security levels. 21–23…”
Section: Introductionmentioning
confidence: 99%
“…By using passive or active materials of different nature (integrated light sources in dielectric or metallic systems), and by playing with the systems' dimensionality (2D or 3D), a large variety of optical PUFs can be conceived, as research in the last decades has demonstrated. This includes PUFs based on organic nano-emitters 21,22 , chip-scale laser 23 , thin random scattering layers of plasmonic nano-particles [24][25][26][27] , random silver nano-structures 28,29 , or even PUFs architecture compatible with microfabrication technologies for photonic integrated circuits (PIC) [30][31][32] . In the end, any material with random structure, defects or scattering elements, including regular paper 33 , will generate complex speckle patterns when illuminated by a coherent source, making optical PUFs a highly efficient, inexpensive and robust platform for secure authentication 5,8,28,34,35 .…”
Section: Introductionmentioning
confidence: 99%